A comparative study of four tree species used in riparian forest restoration along Uruguay River, Brazil Um estudo comparativo entre quatro espécies arbóreas utilizadas na restauração da cobertura florestal ripária do Rio Uruguai - Alexandre Hüller; Geraldo Ceni Coelho; Osório Antônio Lucchese; Jorge Schirmer (Revista Árvore, 2009)
Silvicultural and ecological knowledge about tree species is basic to restoration planning, particularly in high diversity regions. Here we present a comparison of four native tree species from the middle Uruguay River basin, Brazil-Argentine frontier: Heliocarpus americanus L. (Malvaceae), Maclura tinctoria (L.) D. Don ex Steud. (Moraceae), Schinus terebinthifolius Raddi (Anacardiaceae) and Cordia trichotoma (Vell.) Arrab. ex Steud. (Boraginaceae). We obtained data on initial growth, light interception, litterfall and litter mineral contents. H. americanus presented the greatest height and the lowest value of height/crown width ratio. H. americanus and M. tinctoria presented the highest light interception rate (>94 %) and highest litterfall (879 ± 151 and 792 ± 164 g·m-2·year-1, respectively). For the set of species, the lowest litterfall occurred between July and September. H. americanus presented the highest K concentration (1.13%) in the litter, while C. trichotoma had the highest values of Ca and Mg (6.35 and 2.02 %, respectively). S. terebinthifolius had the lowest light interception rate and litter mineral content. O conhecimento silvicultural e ecológico sobre as espécies arbóreas são fundamentais para o planejamento da restauração ecológica em áreas de alta diversidade. Este estudo apresenta uma comparação entre quatro espécies arbóreas nativas da porção média da bacia do rio Uruguai: Heliocarpus americanus L. (Malvaceae), Maclura tinctoria (L.) D. Don ex Steud. (Moraceae), Schinus terebinthifolius Raddi (Anacardiaceae) e Cordia trichotoma (Vell.) Arrab. ex Steud. (Boraginaceae). Foram obtidos dados sobre o crescimento inicial, a interceptação de luz, a produção de serapilheira e o seu conteúdo mineral. H. americanus apresentou maior crescimento em altura e menor razão entre altura e largura de copa. H. americanus e M. tinctoria tiveram a maior interceptação da luz solar (> 94%) e a maior produção de serapilheira (879 ± 151 e 792 ± 164 g·m-2·ano-1, respectivamente). A menor produção de serapilheira, para o conjunto das quatro espécies, ocorreu entre julho e setembro. H. americanus apresentou os maiores teores de K (1,13 %) na serapilheira, enquanto C. trichotoma, os maiores valores de Ca e Mg (6,35 e 2,02%, respectivamente). S. terebinthifolius exibiu a menor interceptação da luz solar e os menores teores de nutrientes minerais na serapilheira.